Situational and Individual Risk Factors for Cybercrime Victimization in a Cross-national Context - Mikkola, Marko (International journal of offender therapy and comparative criminology, 2024)
Routine Activity Theory (RAT) and the general theory of crime have been widely employed to understand cybercrime victimization. However, there is a need to integrate these theoretical frameworks to better understand victimization from a cross-national perspective. A web-based survey was conducted among participants aged 15 to 25 years from the U.S., Finland, Spain, and South Korea. Factors related to RAT were associated with increased victimization in all four countries although results varied between the countries. Low self-control was associated with victimization in the U.S., Finland, and Spain but not in South Korea. Using decomposition analysis, we discovered that the association between low self-control and victimization occurred both directly and indirectly through measures of RAT. Our study demonstrates the need to integrate theories to better understand the dynamics of victimization. Despite the usefulness of RAT, other theories should be taken into consideration when investigating cybercrime victimization.